Komodifikasi Cerita Rakyat pada Media Perangko Indonesia - Kristiana, Nova (Ekspresi, 2010)
The Comodification of Folktale on Stamps in Indonesia. The commodification of folktales on stamps can generate a negotiation between the local culture and the cultural-political interest that benefits the government. Stamp does not only function as a payment device in correspondence or merely to be collected. Moreover, stamp is a site full with the complexity of meanings, messages, and interests. A long series of story is condensed by presenting only the essence of the story and the main meaning. That is why it is hoped that the stamp design simply illustrates the key scene. For PT Pos, it is really hoped that the publishing of the folktales stamps did not stop in 2005, but it can be continued by introducing stories from various regions. Keywords: Perangko, filateli, folk stamp.